A healthy functional bedding composite material based on graphene oxide and preparation method thereof

By introducing starch-based sustained-release essence and aromatic latex materials into the health-functional bedding composite material of graphene oxide, and preparing composite materials by impregnation method, the shortcomings in performance stability and application scope of existing materials are solved, and the effects of long-lasting aroma and strong antibacterial performance are achieved, and the user's sleep experience is improved.

CN119775631APending Publication Date: 2025-04-08HEYE HEALTH TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510073159.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing health-functional bedding composite materials based on graphene oxide have shortcomings in production costs, preparation processes, environmental risks, performance stability and scope of application, and it is difficult to meet the needs of high sleep quality and health functions.

Method used

The starch-based sustained-release flavor and aromatic latex material are combined with graphene oxide to prepare graphene/latex sponge composite material through impregnation method to improve the antibacterial, moisture-absorbing and perspiration of the material and the long-lasting aroma.

Benefits of technology

It realizes the long-lasting aroma of the material, has strong controlled release effect, improves comfort, enhances antibacterial and anti-mites, extends the longevity of the aroma, and enhances the user's sleep experience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775631A_ABST
    Figure CN119775631A_ABST
Patent Text Reader

Abstract

The present invention relates to a healthy functional bedding composite material based on graphene oxide and a preparation method thereof, which includes: preparation of hydrogel, preparation of starch-based slow-release essence, synthesis of composite cationic silicone emulsion, preparation of aromatic latex material, preparation of graphene oxide, preparation of graphene oxide / latex sponge composite material by impregnation method. The present invention creatively combines impregnation method and oxalic acid precipitation method to prepare the obtained healthy functional bedding composite material with health care multifunctional performance. The healthy functional bedding composite material provided by the present invention has excellent comfort and durability, and has the functions of relieving pressure and improving mood.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a healthy functional bedding composite material based on graphene oxide and a preparation method thereof. Background Art

[0002] With the continuous development of materials science and the continuous progress of preparation technology, graphene oxide-based healthy functional bedding composite materials will usher in a wider range of application prospects. In the future, this composite material is expected to play an important role in improving sleep quality, promoting human health, and bringing more convenience and comfort to people's lives. At the same time, with the improvement of environmental awareness and the advancement of sustainable development strategies, this green and environmentally friendly composite material will also become an important development direction in the field of bedding materials.

[0003] Graphene oxide is an important derivative of graphene, with a large number of oxygen-containing groups (such as hydroxyl, carboxyl and epoxy groups) on its surface, which gives it some unique properties; graphene oxide has a very large specific surface area, which provides abundant active sites for adsorption and surface modification; however, graphene oxide-based healthy functional bedding composite materials and their preparation methods have certain disadvantages in terms of production cost, preparation process, environmental risks, performance stability and scope of application.

[0004] As people's living standards improve, their requirements for sleep quality are getting higher and higher. Bedding materials not only need to provide a comfortable sleeping environment, but also need to have certain health functions, such as antibacterial and anti-mite. Traditional bedding materials often have deficiencies in these aspects, so it is particularly important to develop new bedding materials with health functions. Summary of the invention

[0005] In view of the above problems, the present invention provides a healthy functional bedding composite material based on graphene oxide.

[0006] The first technical purpose of the present invention is to provide a starch-based slow-release flavor with lasting fragrance, strong controlled-release effect and improved comfort.

[0007] The second technical purpose of the present invention is to provide a method for preparing a fragrant latex material with good fragrance persistence, improved wear resistance and anti-aging properties.

[0008] The third technical purpose of the present invention is to provide a preparation process of graphene / latex sponge composite materials by impregnation method.

[0009] The present invention provides a method for preparing a healthy functional bedding composite material based on graphene oxide, comprising the following steps: preparing a hydrogel, preparing a starch-based sustained-release flavor, synthesizing a composite cationic silicone emulsion, preparing an aromatic latex material, preparing graphene oxide, and preparing a graphene oxide / latex sponge composite material by an impregnation method.

[0010] Preferably, in step (1), the preparation of the hydrogel Add deionized water to a beaker, stir and heat in a constant temperature water bath, then weigh α-cyclodextrin and add it to the beaker and stir until dissolved, finally add polyethylene glycol and stir to dissolve, take out the sample and cool it at room temperature, and then store it at a certain temperature; Step (2) Preparation of starch-based sustained-release flavor Add OSAS (oxidized starch), HP-β-CD (hydroxypropyl-β-cyclodextrin) and ionized water into a beaker and place it in a water bath to dissolve OSAS and HP-β-CD (water phase) under magnetic stirring, take out and cool to room temperature; add linalool (oil phase) to the water phase using a syringe pump under magnetic stirring, then add the hydrogel prepared in step (1) and stir for a period of time, and finally shear emulsify for a period of time to obtain a starch-based sustained-release flavor; Step (3) Synthesis of composite cationic silicone emulsion The composite emulsifier (hexadecyltrimethylammonium bromide, Tween 80 (polysorbate 80)), monomer D4 (octamethylcyclotetrasiloxane) and deionized water are added into a three-necked flask equipped with a stirrer, a thermometer and a condenser, stirred at a high speed at a certain temperature, heated to a certain degree, added with KOH aqueous solution, reacted at a constant temperature, cooled, and then dripped with glacial acetic acid to neutralize and adjust the pH value, thereby preparing a composite cationic silicone emulsion; Step (4) Preparation of aromatic latex material The amount of CNCs powder added is a certain value, the starch-based slow-release flavor prepared in step (2) is added, the composite cationic silicone emulsion prepared in step (3) is immersed in a container with a certain concentration of slow-release flavor, the sample is taken out after stirring, the sample is frozen and then freeze-dried in a freeze dryer, thereby obtaining a fragrant latex material; Step (5) Preparation of graphene oxide After the concentrated H2SO4 and graphite powder are mixed evenly, KMnO4 is slowly added to the mixed solution in an ice water bath. At this time, the mixed solution is dark green. Stir in a constant temperature water bath, add deionized water after cooling and mix evenly, then add hydrogen peroxide to remove excess KMnO4. At this time, the mixed solution changes from reddish brown to yellow. The solution is taken out and centrifuged to remove unreacted graphite powder, and then centrifuged and washed several times with deionized water until the pH of the supernatant is neutral. The solid is placed in a freeze drying box to obtain sponge-like graphene oxide; Step (6) Preparation of graphene / latex sponge composite material by impregnation method The graphene oxide prepared in step (5) is dispersed in an ethanol solution by ultrasound, and the weighed latex sponge is ultrasonically cleaned several times with acetone and deionized water, and then placed in a vacuum drying oven for drying and weighing. The aromatic latex material and latex sponge prepared in step (4) after cleaning and drying are immersed in the ethanol solution of graphene oxide, soaked at room temperature, stirred, and the pH value is adjusted with ammonia water, and then gallic acid is added, reduced in an oil bath, and the treated sponge is dried to prepare an impregnation method graphene / latex sponge composite material.

[0011] Preferably, in step (1), the preparation of the hydrogel Add 90-100g of deionized water to a beaker, heat to 80-85°C in a constant temperature water bath with stirring, then weigh 9-15g of α-cyclodextrin, add it to the beaker and stir at 600-650r / min until dissolved, finally add 1-9g of polyethylene glycol and stir and dissolve at 650-700r / min for 30-35min, take out the sample and cool it at room temperature for 12-24h, and then store it at 1-4°C.

[0012] The advantages of the present invention are that both α-cyclodextrin and polyethylene glycol are natural materials or materials with good biocompatibility. As a cyclic oligosaccharide, α-cyclodextrin is non-toxic and degradable. Polyethylene glycol is widely used in the fields of medicine and cosmetics and has good biocompatibility. The hydrogel prepared by using these natural or biocompatible materials is harmless to the human body. The optimized preparation process can ensure that α-cyclodextrin and polyethylene glycol are fully dissolved in deionized water to form a uniform hydrogel solution; the prepared hydrogel has good processability and can be easily compounded with other functional materials such as graphene oxide to further enhance the antibacterial, moisture absorption and perspiration properties of the bedding.

[0013] Preferably, step (2) preparation of starch-based slow-release flavor Add OSAS, HP-β-CD and ionized water into a beaker and place it in a 55-60°C water bath, stir magnetically at 600-650 r / min for 1-5 h to dissolve OSAS and HP-β-CD (water phase), take out and cool to room temperature; add linalool (oil phase) to the water phase using a syringe pump under magnetic stirring, then add the hydrogel prepared in step (1) and stir at 650-750 r / min for 25-30 min, and finally shear emulsify at a rate of 9500-10000 r / min for 30-60 min to obtain a starch-based sustained-release flavor.

[0014] The present invention has the advantage that the hydrogel prepared in step (1) is added in this step, and its porous structure helps to adsorb and fix the flavor components, thereby slowing down the release rate of the flavor. This slow-release effect enables the flavor to continue to emit fragrance during use, thereby extending the durability of the fragrance. The emulsification process not only makes the flavor ingredients evenly dispersed in the hydrogel, but also forms tiny emulsion droplets or vesicle structures through shear force. These structures help to further delay the release of the flavor and improve the stability and uniformity of the overall flavor.

[0015] Preferably, step (3) the synthesis of the composite cationic silicone emulsion Add the composite emulsifier (hexadecyltrimethylammonium bromide, Tween 80 (polysorbate 80)), monomer D4 (octamethylcyclotetrasiloxane) and deionized water into a three-necked flask with a stirrer, a thermometer and a condenser, stir at high speed at 45-50°C for 25-30 minutes, heat to 80-85°C, add 10-15% KOH aqueous solution, react at constant temperature for 4-10 hours, cool and add glacial acetic acid dropwise to neutralize to a pH of about 1-7, and prepare a composite cationic silicone emulsion.

[0016] The present invention has the advantage that the combination of the composite emulsifier Tween 80 and other emulsifiers can improve the stability and dispersibility of the emulsion, ensuring the uniform dispersion of the organic silicon components such as the monomer D4 (octamethylcyclotetrasiloxane) in the water phase; Through a specific synthesis process, the silicone emulsion has cationic properties. This cationic emulsion can combine well with negatively charged fibers or surfaces, giving bedding materials special softness, smoothness and antistatic properties, thereby improving the user's sleeping experience.

[0017] Preferably, step (4) preparation of aromatic latex material The CNCs powder is added in an amount of 0.12-0.20 g to the starch-based slow-release flavor prepared in step (2), and the composite cationic silicone emulsion prepared in step (3) is immersed in a container with a slow-release flavor concentration of 5-30%, and the sample is taken out after stirring at 650-700 r / min for 6-12 hours, and the sample is frozen for 12-24 hours and then freeze-dried in a freeze dryer for 12-24 hours to obtain a fragrant latex material.

[0018] The advantage of adopting the present invention is that the addition of CNCs (cellulose nanocrystals) powder not only enhances the structural strength of the latex material, but also serves as a carrier for the sustained release of flavors, which helps to evenly distribute the flavor ingredients in the latex material, which makes the fragrance more lasting and evenly emitted, thereby improving the user's sleep experience.

[0019] The immersion and stirring treatment of the composite cationic silicone emulsion allows the silicone components in the emulsion to penetrate into the interior of the latex material, thereby improving its softness, smoothness, antistatic properties and other properties; the interaction between the cationic emulsion and the surface of the latex material enhances the bonding force between the two, allowing the fragrance components to be more firmly fixed in the latex material, further prolonging the persistence of the fragrance.

[0020] Preferably, step (5) preparation of graphene oxide After 95-100mL of concentrated H2SO4 and 1-5g of graphite powder are mixed evenly, 9-15g of KMnO4 is slowly added to the mixed solution in an ice water bath. At this time, the mixed solution is dark green. It is stirred in a constant temperature water bath of 45-50°C for 12-24h. After cooling, deionized water is added and mixed evenly. Then 5-10mL of hydrogen peroxide is added to remove excess KMnO4. At this time, the mixed solution changes from reddish brown to yellow. The solution is taken out and centrifuged at 3500-4000rpm to remove unreacted graphite powder. Then, deionized water is used for centrifugal washing at 11000-12000rpm for several times until the pH of the supernatant is neutral. The solid is placed in a freeze drying oven for 40-48h to obtain sponge-like graphene oxide.

[0021] The invention has the advantages that unreacted graphite powder and other impurities are effectively removed through multiple centrifugal washings, thereby improving the purity of graphene oxide. At the same time, deionized water is used for washing, thereby avoiding the introduction of new impurities. The washed solid is placed in a freeze drying box for drying, thereby avoiding the destruction of the graphene oxide structure and the degradation of the performance caused by traditional heating drying, thereby further improving the purity of the product.

[0022] Preferably, step (6) preparation of graphene / latex sponge composite material by impregnation method The graphene oxide prepared in step (5) is dispersed in 45-50 mL of ethanol solution by ultrasound, and the weighed latex sponge is ultrasonically cleaned several times with acetone and deionized water, and then placed in a vacuum drying oven for drying and weighed, with an error of no more than 0.01-0.06 g. The aromatic latex material and latex sponge prepared in step (4) after cleaning and drying are immersed in the ethanol solution of graphene oxide, soaked at room temperature for 1-5 hours, stirred for 1-5 hours, and then adjusted to a pH of 5-12 with ammonia water, and then 0.1-0.4 g of gallic acid is added, and reduced in an oil bath at 90-95°C for 6-12 hours. The treated sponge is dried to prepare an impregnation graphene / latex sponge composite material.

[0023] The advantage of the present invention is that the cleaned and dried aromatic latex material and latex sponge are immersed in an ethanol solution of graphene oxide, and through immersion and stirring, the graphene can fully penetrate into the internal structure of the latex sponge to form a strong bond, thereby improving the overall performance of the composite material.

[0024] In summary, the present invention has the following beneficial effects: 1. The advantages of the present invention are that both α-cyclodextrin and polyethylene glycol are natural or biocompatible materials. As a cyclic oligosaccharide, α-cyclodextrin is non-toxic and degradable. Polyethylene glycol is widely used in the fields of medicine and cosmetics and has good biocompatibility. The hydrogel prepared using these natural or biocompatible materials is harmless to the human body. 2. The advantages of the present invention are that, through the optimized preparation process, α-cyclodextrin and polyethylene glycol can be fully dissolved in deionized water to form a uniform hydrogel solution; the prepared hydrogel has good processability and can be easily compounded with other functional materials such as graphene oxide to further improve the antibacterial, moisture absorption and perspiration properties of the bedding; 3. The present invention has the advantage that the hydrogel prepared in step (1) is added in this step, and its porous structure helps to adsorb and fix the flavor components, thereby slowing down the release rate of the flavor. This slow-release effect enables the flavor to continue to emit fragrance during use, thereby extending the durability of the fragrance; 4. The present invention has the advantage that the emulsification process not only makes the flavor components evenly dispersed in the hydrogel, but also forms tiny emulsion droplets or vesicle structures through the shear force, which helps to further delay the release of the flavor and improve the stability and uniformity of the overall flavor; 5. The present invention has the advantage that the combination of the composite emulsifier Tween 80 and other emulsifiers can improve the stability and dispersibility of the emulsion, ensuring the uniform dispersion of the organosilicon components such as the monomer D4 (octamethylcyclotetrasiloxane) in the water phase; 6. The advantage of the present invention is that, through a specific synthesis process, the organosilicon emulsion has cationic properties. This cationic emulsion can be well combined with negatively charged fibers or surfaces, giving the bedding material special softness, smoothness and antistatic properties, thereby improving the user's sleeping experience; 7. The invention has the advantage that the addition of CNCs (cellulose nanocrystals) powder not only enhances the structural strength of the latex material, but also acts as a carrier for the slow-release flavor, which helps to evenly distribute the flavor ingredients in the latex material, making the fragrance more lasting and evenly distributed, thus improving the user's sleeping experience; 8. The present invention has the advantages that the immersion and stirring treatment of the composite cationic silicone emulsion allows the silicone component in the emulsion to penetrate into the interior of the latex material, thereby improving its softness, smoothness, antistatic properties and other properties; the interaction between the cationic emulsion and the surface of the latex material enhances the binding force between the two, so that the fragrance component is more firmly fixed in the latex material, further extending the persistence of the fragrance; 9. The present invention has the advantages that, by multiple centrifugal washings, unreacted graphite powder and other impurities are effectively removed, thereby improving the purity of graphene oxide. At the same time, deionized water is used for washing to avoid the introduction of new impurities. The washed solid is placed in a freeze drying box for drying, thereby avoiding the destruction of the graphene oxide structure and the degradation of its performance caused by conventional heating drying, thereby further improving the purity of the product. 10. The advantage of the present invention is that the cleaned and dried aromatic latex material and latex sponge are immersed in an ethanol solution of graphene oxide. Through soaking and stirring, the graphene can fully penetrate into the internal structure of the latex sponge to form a strong bond, thereby improving the overall performance of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The invention relates to a healthy functional bedding composite material based on graphene oxide and a preparation process thereof. DETAILED DESCRIPTION

[0026] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention are within the scope of the present invention.

[0027] If not specifically stated, the technical means used in the examples are conventional means known to those skilled in the art. In addition, all the raw materials used in the examples are known commercial products.

[0028] Example 1

[0029] Step (1) Preparation of hydrogel Add 90g of deionized water to a beaker, heat to 80°C in a constant temperature water bath, then weigh 9g of α-cyclodextrin and add it to the beaker and stir at 600r / min until dissolved, finally add 1g of polyethylene glycol and stir and dissolve at 650r / min for 30min, take out the sample and cool it at room temperature for 12h, then store it at 1°C; Step (2) Preparation of starch-based sustained-release flavor Add OSAS, HP-β-CD and ionized water to a beaker and place it in a 55°C water bath, stir magnetically at 600 r / min for 1 h to dissolve OSAS and HP-β-CD (water phase), take it out and cool it to room temperature; add linalool (oil phase) to the water phase using a syringe pump under magnetic stirring, then add the hydrogel prepared in step (1) and stir at 650 r / min for 25 min, and finally shear emulsify at a rate of 9500 r / min for 30 min, thereby obtaining a starch-based sustained-release flavor; Step (3) Synthesis of composite cationic silicone emulsion The composite emulsifier (hexadecyltrimethylammonium bromide, Tween 80 (polysorbate 80)), monomer D4 (octamethylcyclotetrasiloxane) and deionized water were added into a three-necked flask equipped with a stirrer, a thermometer and a condenser, stirred at high speed at 45°C for 25 minutes, heated to 80°C, added with 10% KOH aqueous solution, reacted at constant temperature for 4 hours, cooled, and then dripped with glacial acetic acid to neutralize to a pH of about 1, thereby preparing a composite cationic silicone emulsion; Step (4) Preparation of aromatic latex material The CNCs powder is added in an amount of 0.12 g to the starch-based slow-release flavor prepared in step (2), and the composite cationic silicone emulsion prepared in step (3) is immersed in a container with a slow-release flavor concentration of 5%, and the sample is taken out after stirring at 650 r / min for 6 hours, and the sample is frozen for 12 hours and then freeze-dried in a freeze dryer for 12 hours to obtain a fragrant latex material; Step (5) Preparation of graphene oxide After 95 mL of concentrated H2SO4 and 1 g of graphite powder are mixed evenly, 9 g of KMnO4 is slowly added to the mixed solution in an ice water bath. At this time, the mixed solution is dark green. Stir in a constant temperature water bath at 45°C for 12 hours. After cooling, deionized water is added and mixed evenly. Then 5 mL of hydrogen peroxide is added to remove excess KMnO4. At this time, the mixed solution changes from reddish brown to yellow. The solution is taken out and centrifuged at 3500 rpm to remove unreacted graphite powder. Then, deionized water is used for centrifugal washing at 11000 rpm for several times until the pH of the supernatant is neutral. The solid is placed in a freeze drying oven for 40 hours to obtain sponge-like graphene oxide. Step (6) Preparation of graphene / latex sponge composite material by impregnation method The graphene oxide prepared in step (5) is dispersed in 46 mL of ethanol solution by ultrasound, and the weighed latex sponge is ultrasonically cleaned several times with acetone and deionized water, and then placed in a vacuum drying oven for drying and weighed, with an error of no more than 0.02 g. The aromatic latex material and latex sponge prepared in step (4) after cleaning and drying are immersed in the ethanol solution of graphene oxide, soaked at room temperature for 2 h, stirred for 5 h, and then adjusted to pH 6 with ammonia water, and then 0.2 g of gallic acid is added, and reduced in an oil bath at 91°C for 7 h. The treated sponge is dried to prepare an impregnation graphene / latex sponge composite material.

[0030] Example 2 Step (1) Preparation of hydrogel Add 92g of deionized water to a beaker, stir and heat to 81°C in a constant temperature water bath, then weigh 10g of α-cyclodextrin and add it to the beaker and stir at a rate of 610r / min until dissolved, finally add 2g of polyethylene glycol and stir and dissolve at a rate of 660r / min for 32min, take out the sample and cool it at room temperature for 15h, and then store it at 2°C; Step (2) Preparation of starch-based sustained-release flavor Add OSAS, HP-β-CD and ionized water into a beaker and place it in a 56°C water bath, stir magnetically at 610 r / min for 2 h to dissolve OSAS and HP-β-CD (water phase), take out and cool to room temperature; add linalool (oil phase) to the water phase using a syringe pump under magnetic stirring, then add the hydrogel prepared in step (1) and stir at 660 r / min for 26 min, and finally shear emulsify at a rate of 9500 r / min for 35 min, thereby obtaining a starch-based sustained-release flavor; Step (3) Synthesis of composite cationic silicone emulsion The composite emulsifier (hexadecyltrimethylammonium bromide, Tween 80 (polysorbate 80)), monomer D4 (octamethylcyclotetrasiloxane) and deionized water were added into a three-necked flask equipped with a stirrer, a thermometer and a condenser, stirred at high speed at 46°C for 26 minutes, heated to 82°C, added with 12% KOH aqueous solution, reacted at constant temperature for 5 hours, cooled, and neutralized with glacial acetic acid dropwise to a pH of about 2, thereby preparing a composite cationic silicone emulsion; Step (4) Preparation of aromatic latex material The CNCs powder is added in an amount of 0.15 g to the starch-based slow-release flavor prepared in step (2), and the composite cationic silicone emulsion prepared in step (3) is immersed in a container with a slow-release flavor concentration of 6%, and the sample is taken out after stirring at 660 r / min for 10 hours, and the sample is frozen for 12 hours and then freeze-dried in a freeze dryer for 24 hours to obtain a fragrant latex material; Step (5) Preparation of graphene oxide After 96 mL of concentrated H2SO4 and 5 g of graphite powder are mixed evenly, 10 g of KMnO4 is slowly added to the mixed solution in an ice water bath. At this time, the mixed solution is dark green. Stir in a constant temperature water bath at 46 ° C for 12 hours. After cooling, deionized water is added to mix evenly. Then 6 mL of hydrogen peroxide is added to remove excess KMnO4. At this time, the mixed solution changes from reddish brown to yellow. The solution is taken out and centrifuged at 3600 rpm to remove unreacted graphite powder. Then, deionized water is used for centrifugal washing at 11000 rpm for several times until the pH of the supernatant is neutral. The solid is placed in a freeze drying box for 42 hours to obtain sponge-like graphene oxide. Step (6) Preparation of graphene / latex sponge composite material by impregnation method The graphene oxide prepared in step (5) is dispersed in 46 mL of ethanol solution by ultrasound, and the weighed latex sponge is ultrasonically cleaned several times with acetone and deionized water, and then placed in a vacuum drying oven for drying and weighed, with an error of no more than 0.03 g. The aromatic latex material and latex sponge prepared in step (4) after cleaning and drying are immersed in the ethanol solution of graphene oxide, soaked at room temperature for 3 h, stirred for 2 h, and then adjusted to pH 10 with ammonia water, and then 0.3 g of gallic acid is added, and reduced in a 93°C oil bath for 7 h. The treated sponge is dried to prepare an impregnation graphene / latex sponge composite material.

[0031] Example 3 Step (1) Preparation of hydrogel Add 100 g of deionized water to a beaker, heat to 80°C in a constant temperature water bath, then weigh 9 g of α-cyclodextrin and add it to the beaker and stir at 650 r / min until dissolved, finally add 9 g of polyethylene glycol and stir and dissolve at 650 r / min for 30 min, take out the sample and cool it at room temperature for 24 h, and then store it at 4°C; Step (2) Preparation of starch-based sustained-release flavor Add OSAS, HP-β-CD and ionized water into a beaker and place it in a 60°C water bath, stir magnetically at 650 r / min for 1 h to dissolve OSAS and HP-β-CD (water phase), take out and cool to room temperature; add linalool (oil phase) to the water phase using a syringe pump under magnetic stirring, then add the hydrogel prepared in step (1) and stir at 650 r / min for 30 min, finally shear emulsify at a rate of 10000 r / min for 30 min, thereby obtaining a starch-based sustained-release flavor; Step (3) Synthesis of composite cationic silicone emulsion The composite emulsifier (hexadecyltrimethylammonium bromide, Tween 80 (polysorbate 80)), monomer D4 (octamethylcyclotetrasiloxane) and deionized water were added into a three-necked flask equipped with a stirrer, a thermometer and a condenser, stirred at high speed at 50°C for 30 minutes, heated to 80°C, added with 10% KOH aqueous solution, reacted at constant temperature for 4 hours, cooled, and then dripped with glacial acetic acid to neutralize to a pH of about 7, thereby preparing a composite cationic silicone emulsion; Step (4) Preparation of aromatic latex material The CNCs powder is added in an amount of 0.12 g to the starch-based slow-release flavor prepared in step (2), and the composite cationic silicone emulsion prepared in step (3) is immersed in a container with a slow-release flavor concentration of 10%, and the sample is taken out after stirring at 650 r / min for 12 hours, and the sample is frozen for 24 hours and then freeze-dried in a freeze dryer for 24 hours to obtain a fragrant latex material; Step (5) Preparation of graphene oxide After 100 mL of concentrated H2SO4 and 1 g of graphite powder are mixed evenly, 9 g of KMnO4 is slowly added to the mixed solution in an ice water bath. At this time, the mixed solution is dark green. Stir in a constant temperature water bath at 45°C for 24 hours. After cooling, add deionized water and mix evenly. Then add 10 mL of hydrogen peroxide to remove excess KMnO4. At this time, the mixed solution changes from reddish brown to yellow. Take out the solution and centrifuge at 4000 rpm to remove unreacted graphite powder. Then, use deionized water at 12000 rpm to centrifuge and wash several times until the pH of the supernatant is neutral. Place the solid in a freeze drying oven for 48 hours to obtain sponge-like graphene oxide. Step (6) Preparation of graphene / latex sponge composite material by impregnation method The graphene oxide prepared in step (5) is dispersed in 50 mL of ethanol solution by ultrasound, and the weighed latex sponge is ultrasonically cleaned several times with acetone and deionized water, and then placed in a vacuum drying oven for drying and weighed, with an error of no more than 0.01 g. The aromatic latex material and latex sponge prepared in step (4) after cleaning and drying are immersed in the ethanol solution of graphene oxide, soaked at room temperature for 1 hour, stirred for 1 hour, and then adjusted to pH 12 with ammonia water, and then 0.2 g of gallic acid is added, and reduced in a 95°C oil bath for 7 hours. The treated sponge is dried to prepare an impregnation graphene / latex sponge composite material.

[0032] Example 4 Step (1) Preparation of hydrogel Add 100 g of deionized water to a beaker, heat to 85°C in a constant temperature water bath, then weigh 15 g of α-cyclodextrin and add it to the beaker and stir at 650 r / min until dissolved, finally add 9 g of polyethylene glycol and stir at 700 r / min for 35 min, take out the sample and cool it at room temperature for 24 h, then store it at 4°C; Step (2) Preparation of starch-based sustained-release flavor Add OSAS, HP-β-CD and ionized water to a beaker and place it in a 60°C water bath, stir magnetically at 650 r / min for 5 h to dissolve OSAS and HP-β-CD (water phase), take it out and cool it to room temperature; add linalool (oil phase) to the water phase using a syringe pump under magnetic stirring, then add the hydrogel prepared in step (1) and stir at 750 r / min for 25 min, and finally shear emulsify at a rate of 10000 r / min for 60 min, thereby obtaining a starch-based sustained-release flavor; Step (3) Synthesis of composite cationic silicone emulsion The composite emulsifier (hexadecyltrimethylammonium bromide, Tween 80 (polysorbate 80)), monomer D4 (octamethylcyclotetrasiloxane) and deionized water were added into a three-necked flask equipped with a stirrer, a thermometer and a condenser, stirred at high speed for 30 minutes at 50°C, heated to 85°C, added with 15% KOH aqueous solution, reacted at constant temperature for 10 hours, cooled, and neutralized by dropwise addition of glacial acetic acid to a pH of about 7, thereby preparing a composite cationic silicone emulsion; Step (4) Preparation of aromatic latex material The CNCs powder is added in an amount of 0.20 g to the starch-based slow-release flavor prepared in step (2), and the composite cationic silicone emulsion prepared in step (3) is immersed in a container with a slow-release flavor concentration of 30%, and the sample is taken out after stirring at 700 r / min for 12 hours, and the sample is frozen for 24 hours and then freeze-dried in a freeze dryer for 24 hours to obtain a fragrant latex material; Step (5) Preparation of graphene oxide After 100 mL of concentrated H2SO4 and 5 g of graphite powder are mixed evenly, 15 g of KMnO4 is slowly added to the mixed solution in an ice water bath. At this time, the mixed solution is dark green. Stir in a constant temperature water bath at 50°C for 24 hours. After cooling, deionized water is added and mixed evenly. Then 6 mL of hydrogen peroxide is added to remove excess KMnO4. At this time, the mixed solution changes from reddish brown to yellow. The solution is taken out and centrifuged at 4000 rpm to remove unreacted graphite powder. Then, deionized water is used for centrifugal washing at 12000 rpm for several times until the pH of the supernatant is neutral. The solid is placed in a freeze drying oven for 48 hours to obtain sponge-like graphene oxide. Step (6) Preparation of graphene / latex sponge composite material by impregnation method The graphene oxide prepared in step (5) is dispersed in 50 mL of ethanol solution by ultrasound, and the weighed latex sponge is ultrasonically cleaned several times with acetone and deionized water, and then placed in a vacuum drying oven for drying and weighed, with an error of no more than 0.06 g. The aromatic latex material and latex sponge prepared in step (4) after cleaning and drying are immersed in the ethanol solution of graphene oxide, soaked at room temperature for 5 h, stirred for 5 h, and then adjusted to pH 12 with ammonia water, and then 0.4 g of gallic acid is added, and reduced in a 95°C oil bath for 12 h. The treated sponge is dried to prepare an impregnation graphene / latex sponge composite material.

[0033] Comparative Example 1 Step (1) Preparation of hydrogel Add 110 g of deionized water to a beaker, heat to 95°C in a constant temperature water bath, then weigh 20 g of α-cyclodextrin and add it to the beaker and stir at 650 r / min until dissolved, finally add 15 g of polyethylene glycol and stir and dissolve at 660 r / min for 60 min, take out the sample and cool it at room temperature for 24 h, and then store it at 2°C; Step (2) Preparation of starch-based sustained-release flavor Add OSAS, HP-β-CD and ionized water into a beaker and place it in a 65°C water bath, stir magnetically at 650 r / min for 10 h to dissolve OSAS and HP-β-CD (water phase), take it out and cool it to room temperature; add linalool (oil phase) to the water phase using a syringe pump under magnetic stirring, then add the hydrogel prepared in step (1) and stir at 660 r / min for 35 min, and finally shear emulsify at a rate of 9600 r / min for 120 min, thereby obtaining a starch-based sustained-release flavor; Step (3) Preparation of aromatic latex material The CNCs powder is added in an amount of 0.20 g to the starch-based slow-release flavor prepared in step (2), and immersed in a container with a slow-release flavor concentration of 6%. After stirring at 700 r / min for 12 hours, the sample is taken out, and the sample is frozen for 24 hours and then freeze-dried in a freeze dryer for 24 hours to obtain a fragrant latex material; Step (4) Preparation of graphene oxide After 95 mL of concentrated H2SO4 and 10 g of graphite powder are mixed evenly, 20 g of KMnO4 is slowly added to the mixed solution in an ice water bath. At this time, the mixed solution is dark green. Stir in a constant temperature water bath at 50°C for 24 hours. After cooling, add deionized water and mix evenly. Then add 10 mL of hydrogen peroxide to remove excess KMnO4. At this time, the mixed solution changes from reddish brown to yellow. Take out the solution and centrifuge at 4500 rpm to remove unreacted graphite powder. Then, use deionized water at 12000 rpm to centrifuge and wash several times until the pH of the supernatant is neutral. Place the solid in a freeze drying oven for 48 hours to obtain sponge-like graphene oxide. Step (5) Preparation of graphene / latex sponge composite material by impregnation method The graphene oxide prepared in step (4) is dispersed in 60 mL of ethanol solution by ultrasound, and the weighed latex sponge is ultrasonically cleaned several times with acetone and deionized water, and then placed in a vacuum drying oven for drying and weighed, with an error of no more than 0.08 g. The aromatic latex material and latex sponge prepared in step (3) after cleaning and drying are immersed in the ethanol solution of graphene oxide, soaked at room temperature for 6 h, stirred for 10 h, and then adjusted to pH 12 with ammonia water, and then 0.5 g of gallic acid is added, and reduced in a 95°C oil bath for 12 h. The treated sponge is dried to prepare an impregnation graphene / latex sponge composite material.

[0034] Comparative Example 2

[0035] Step (1) Preparation of hydrogel Add 85g of deionized water to a beaker, heat to 75°C in a constant temperature water bath, then weigh 5g of α-cyclodextrin and add it to the beaker and stir at 550r / min until dissolved, finally add 2g of polyethylene glycol and stir at 500r / min for 25min, take out the sample and cool it at room temperature for 12h, then store it at 2°C; Step (2) Synthesis of composite cationic silicone emulsion The composite emulsifier (hexadecyltrimethylammonium bromide, Tween 80 (polysorbate 80)), monomer D4 (octamethylcyclotetrasiloxane) and deionized water were added into a three-necked flask equipped with a stirrer, a thermometer and a condenser, stirred at high speed for 20 minutes at 30°C, heated to 75°C, added with a 5% KOH aqueous solution, reacted at a constant temperature for 2 hours, cooled, and then dripped with glacial acetic acid to neutralize to a pH of about 2, thereby preparing a composite cationic silicone emulsion; Step (3) Preparation of aromatic latex material The CNCs powder is added in an amount of 0.12 g to the hydrogel prepared in step (1), and the composite cationic silicone emulsion prepared in step (2) is immersed in a container with a sustained-release flavor concentration of 10%, and the sample is taken out after stirring at 600 r / min for 5 hours, and the sample is frozen for 5 hours and then freeze-dried in a freeze dryer for 6 hours to obtain a fragrant latex material; Step (4) Preparation of graphene oxide After 90 mL of concentrated H2SO4 and 1 g of graphite powder are mixed evenly, 5 g of KMnO4 is slowly added to the mixed solution in an ice water bath. At this time, the mixed solution is dark green. Stir in a constant temperature water bath at 35°C for 12 h. After cooling, deionized water is added and mixed evenly. Then 2 mL of hydrogen peroxide is added to remove excess KMnO4. At this time, the mixed solution changes from reddish brown to yellow. The solution is taken out and centrifuged at 3500 rpm to remove unreacted graphite powder. Then, deionized water is used for centrifugal washing at 11000 rpm for several times until the pH of the supernatant is neutral. The solid is placed in a freeze drying oven for 35 h to obtain sponge-like graphene oxide. Step (5) Preparation of graphene / latex sponge composite material by impregnation method The graphene oxide prepared in step (4) is dispersed in 35 mL of ethanol solution by ultrasound, and the weighed latex sponge is ultrasonically cleaned several times with acetone and deionized water, and then placed in a vacuum drying oven for drying and weighed, with an error of no more than 0.02 g. The aromatic latex material and latex sponge prepared in step (3) after cleaning and drying are immersed in the ethanol solution of graphene oxide, soaked at room temperature for 2 h, stirred for 2 h, and then adjusted to pH 2 with ammonia water, and then 0.1 g of gallic acid is added, and reduced in a 90°C oil bath for 6 h. The treated sponge is dried to prepare an impregnation graphene / latex sponge composite material.

[0036] Comparison of detection experiments: The impregnation graphene / latex sponge composites obtained in Examples 1 to 4 and Comparative Example Products 1 and 2 were tested. The specific testing method is as follows: Antibacterial performance test The antibacterial properties of composite materials are evaluated by contacting them with specific bacterial species and observing their growth. Commonly used test species include Escherichia coli and Staphylococcus aureus. First, a certain concentration of target bacterial solution is prepared as the initial bacterial solution; the sample is mixed with the bacterial solution and cultured under appropriate conditions (such as constant temperature and shaking at 37°C). After the culture is completed, the number of surviving colonies is determined by the colony counting method. The antibacterial effect of the sample is calculated by comparing it with the number of bacteria in the initial bacterial solution.

[0037] Anti-aging performance test When latex sponge materials are exposed to air for a long time, aging will inevitably occur, resulting in a decrease in their mechanical properties, which in turn affects their performance and fatigue life. This is mainly because the material undergoes chemical reactions such as oxidation and degradation in an aerobic environment. Therefore, in the reliability study of sponges, the influence of thermal aging cannot be ignored. Temperature and time are the main factors affecting the degree of thermal aging of latex sponges. The purpose of studying the thermal aging degradation law of sponges is to explore their mechanical properties. The aging temperature used in this paper is 100°C and the aging time is 24h. Sustained release performance test The sustained-release performance of flavors can be evaluated by measuring the amount of flavors released at different time points. Gas chromatography (GC) or high-performance liquid chromatography (HPLC) can be used for analysis. The prepared starch-based sustained-release flavors are placed in a certain volume of release medium (such as deionized water, simulated body fluid, etc.), and samples are taken regularly to determine the concentration of the flavors in the release medium, thereby calculating the amount of flavors released.

[0038] Table 1 Antibacterial properties

[0039] As can be seen from Table 1, Example 2 is the best and Comparative Example 2 is the worst. The comparative example has the lowest antibacterial performance, while the example has good antibacterial performance. The graphene oxide in the example has excellent antibacterial performance due to its unique structure. By compounding graphene oxide with latex sponge, the antibacterial performance of graphene oxide can be introduced into the latex sponge, thereby facilitating the improvement of the antibacterial performance of the latex sponge. This composite material can effectively inhibit the growth of bacteria when applied to products such as bedding, and the antibacterial performance can effectively inhibit the growth of bacteria on the surface and inside of bedding, which helps to reduce health risks such as skin infections and respiratory diseases caused by bacterial growth.

[0040] Table 2 Anti-aging performance test

[0041] As can be seen from Table 2, Example 2 is the best and Comparative Example 2 is the worst. The crosslinking density and internal structure of the hydrogel in the examples have an important influence on the tensile stress. A higher crosslinking density can provide better structural stability, reduce shrinkage and deformation caused by water evaporation or environmental changes, and thus enhance anti-aging performance; the interface bonding strength between the graphene and the latex sponge in the examples is conducive to improving the overall stability and anti-aging performance of the composite material.

[0042] Table 3 Sustained release performance

[0043] As can be seen from Table 3, Example 2 is the best and Comparative Example 2 is the worst. The sustained release of the starch-based sustained-release fragrance in Example 2 can ensure that the bedding continuously and stably releases fragrance during use, thereby maintaining a pleasant odor environment for a long time and improving the user's sleep experience. The sustained-release fragrance contains ingredients that are beneficial to the human body; the emulsification process of the fragrance affects the release rate of the fragrance. Smaller droplets usually mean a faster release rate, while larger droplets lead to a slower release.

[0044] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to the present embodiment as needed, but they are protected by patent law as long as they are within the scope of the claims of the present invention.

Claims

1. A healthy functional bedding composite material based on graphene oxide and a preparation method thereof, characterized in that: include: Preparation of hydrogels, preparation of starch-based sustained-release flavors, synthesis of composite cationic silicone emulsions, preparation of aromatic latex materials, preparation of graphene oxide, and preparation of graphene oxide / latex sponge composites by impregnation method.

2. The healthy functional bedding composite material based on graphene oxide and the preparation method thereof according to claim 1, characterized in that: Step (1) Preparation of hydrogel Add deionized water to a beaker, stir and heat in a constant temperature water bath, then weigh α-cyclodextrin and add it to the beaker and stir until dissolved, finally add polyethylene glycol and stir to dissolve, take out the sample and cool it at room temperature, and then store it at a certain temperature; Step (2) Preparation of starch-based sustained-release flavor Add OSAS (oxidized starch), HP-β-CD (hydroxypropyl-β-cyclodextrin) and ionized water into a beaker and place it in a water bath to dissolve OSAS and HP-β-CD (water phase) under magnetic stirring, take out and cool to room temperature; add linalool (oil phase) to the water phase using a syringe pump under magnetic stirring, then add the hydrogel prepared in step (1) and stir for a period of time, and finally shear emulsify for a period of time to obtain a starch-based sustained-release flavor; Step (3) Synthesis of composite cationic silicone emulsion The composite emulsifier (hexadecyltrimethylammonium bromide, Tween 80 (polysorbate 80)), monomer D4 (octamethylcyclotetrasiloxane) and deionized water are added into a three-necked flask equipped with a stirrer, a thermometer and a condenser, stirred at a high speed at a certain temperature, heated to a certain degree, and KOH (potassium hydroxide) aqueous solution is added to react at a constant temperature, cooled, and glacial acetic acid is added dropwise to neutralize and adjust the pH value, thereby preparing a composite cationic silicone emulsion; Step (4) Preparation of aromatic latex material The amount of CNCs (cellulose nanocrystals) powder added is a certain value, the starch-based slow-release flavor prepared in step (2) is added, the composite cationic silicone emulsion prepared in step (3) is immersed in a container with a certain concentration of slow-release flavor, the sample is taken out after stirring, the sample is frozen and then freeze-dried in a freeze dryer, thereby obtaining a fragrant latex material; Step (5) Preparation of graphene oxide After the concentrated H2SO4 (sulfuric acid) and graphite powder are mixed evenly, KMnO4 (potassium permanganate) is slowly added to the mixed solution in an ice water bath. At this time, the mixed solution is dark green. Stir in a constant temperature water bath, add deionized water after cooling and mix evenly, then add hydrogen peroxide to remove excess KMnO4. At this time, the mixed solution changes from reddish brown to yellow. The solution is taken out and centrifuged to remove unreacted graphite powder, and then centrifuged and washed several times with deionized water until the pH of the supernatant is neutral. The solid is placed in a freeze drying box to obtain sponge-like graphene oxide. Step (6) Preparation of graphene / latex sponge composite material by impregnation method The graphene oxide prepared in step (5) is dispersed in an ethanol solution by ultrasound, and the weighed latex sponge is ultrasonically cleaned several times with acetone and deionized water, and then placed in a vacuum drying oven for drying and weighing. The aromatic latex material and latex sponge prepared in step (4) after cleaning and drying are immersed in the ethanol solution of graphene oxide, soaked at room temperature, stirred, and the pH value is adjusted with ammonia water, and then gallic acid is added, reduced in an oil bath, and the treated sponge is dried to prepare an impregnation method graphene / latex sponge composite material.

3. The healthy functional bedding composite material based on graphene oxide and the preparation method thereof according to claim 2, characterized in that: Step (1) Preparation of hydrogel Add 90-100g of deionized water to a beaker, heat to 80-85°C in a constant temperature water bath with stirring, then weigh 9-15g of α-cyclodextrin, add it to the beaker and stir at a rate of 600-650r / min until dissolved, finally add 1-9g of polyethylene glycol and stir and dissolve at a rate of 650-700r / min for 30-35min, take out the sample, cool it at room temperature for 12-24h, and then store it at 1-4°C.

4. The healthy functional bedding composite material based on graphene oxide and the preparation method thereof according to claim 3, characterized in that: Step (2) Preparation of starch-based sustained-release flavor Add OSAS, HP-β-CD and ionized water into a beaker and place it in a 55-60°C water bath, stir magnetically at 600-650 r / min for 1-5 h to dissolve OSAS and HP-β-CD (water phase), take out and cool to room temperature; add linalool (oil phase) to the water phase using a syringe pump under magnetic stirring, then add the hydrogel prepared in step (1) and stir at 650-750 r / min for 25-30 min, and finally shear emulsify at a rate of 9500-10000 r / min for 30-60 min to obtain a starch-based sustained-release flavor.

5. The healthy functional bedding composite material based on graphene oxide and the preparation method thereof according to claim 2, characterized in that: Step (3) Synthesis of composite cationic silicone emulsion Add the composite emulsifier (hexadecyltrimethylammonium bromide, Tween 80 (polysorbate 80)), monomer D4 (octamethylcyclotetrasiloxane) and deionized water into a three-necked flask with a stirrer, a thermometer and a condenser, stir at high speed at 45-50°C for 25-30 minutes, heat to 80-85°C, add 10-15% KOH aqueous solution, react at constant temperature for 4-10 hours, cool and add glacial acetic acid dropwise to neutralize to a pH of about 1-7, and prepare a composite cationic silicone emulsion.

6. The healthy functional bedding composite material based on graphene oxide and the preparation method thereof according to claim 5, characterized in that: Step (4) Preparation of aromatic latex material The CNCs powder is added in an amount of 0.12-0.20 g to the starch-based slow-release flavor prepared in step (2), and the composite cationic silicone emulsion prepared in step (3) is immersed in a container with a slow-release flavor concentration of 5-30%, and the sample is taken out after stirring at 650-700 r / min for 6-12 hours, and the sample is frozen for 12-24 hours and then freeze-dried in a freeze dryer for 12-24 hours to obtain a fragrant latex material.

7. The healthy functional bedding composite material based on graphene oxide and the preparation method thereof according to claim 6, characterized in that: Step (5) Preparation of graphene oxide After 95-100mL of concentrated H2SO4 and 1-5g of graphite powder are mixed evenly, 9-15g of KMnO4 is slowly added to the mixed solution in an ice water bath. At this time, the mixed solution is dark green. It is stirred in a constant temperature water bath of 45-50°C for 12-24h. After cooling, deionized water is added and mixed evenly. Then 5-10mL of hydrogen peroxide is added to remove excess KMnO4. At this time, the mixed solution changes from reddish brown to yellow. The solution is taken out and centrifuged at 3500-4000rpm to remove unreacted graphite powder. Then, deionized water is used for centrifugal washing at 11000-12000rpm for several times until the pH of the supernatant is neutral. The solid is placed in a freeze drying oven for 40-48h to obtain sponge-like graphene oxide.

8. The healthy functional bedding composite material based on graphene oxide and the preparation method thereof according to claim 7, characterized in that: Step (6) Preparation of graphene / latex sponge composite material by impregnation method The graphene oxide prepared in step (5) is dispersed in 45-50 mL of ethanol solution by ultrasound, and the weighed latex sponge is ultrasonically cleaned several times with acetone and deionized water, and then placed in a vacuum drying oven for drying and weighed, with an error of no more than 0.01-0.06 g. The aromatic latex material and latex sponge prepared in step (4) after cleaning and drying are immersed in the ethanol solution of graphene oxide, soaked at room temperature for 1-5 hours, stirred for 1-5 hours, and then adjusted to a pH of 5-12 with ammonia water, and then 0.1-0.4 g of gallic acid is added, and reduced in an oil bath at 90-95°C for 6-12 hours. The treated sponge is dried to prepare an impregnation graphene / latex sponge composite material.